(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
The article assesses how socio-agricultural development will sustain as a result of a balanced scale of rural-urban equality. However, increasing migration from rural to urban areas highly affects productivity and the infrastructure of the productivity in urban sectors. The process of modernization is highly responsible for the change, and a motivator for rural-urban migration not only in Iran, but in China, India and many other developing countries. The emerging scenario is contributing to increasing issues. The article concludes that rural and urban, or so to say, agriculture and industry benefit each other. The paper reaches the point that rural-urban balance optimistically leads to socio-economic development and sustainable growth. On the other hand, increasing and unbridled urbanization leads to declining raw materials needed for industrial development and urban productivity. The article reflects the merits, demerits and the challenges of the current transformation.